STATISTICAL SIGNIFICANCE OF THREE INCISIONAL HERNIA FACTORS - Nasir, Ammad Uddin; Shukr, Irfan (Pakistan Armed Forces Medical Journal, 2021)
Objective: To find out statistical significance of wound infection, use of absorbable suture material and obesity in causation of incisional hernia. Design: A case-control comparative study. Place and Duration of Study: Combined Military Hospitals Rawalpindi and Peshawar from 01 Jan 2000 to 31 Dec 2002. Subjects and Methods: In total 93 patients with incisional hernia were reviewed. A control group of 90 patients was also included in the study, which was operated during the same period who did not develop incisional hernia but had similar selection criteria otherwise. Patients of study group having post operative wound infection, in whom absorbable suture material was used and who were obese were cross tabulated with patients of control group having no incisional hernia, to identify statistically significant variables between these groups by calculating P value for these three factors. P value of < 0.01 was considered highly significant, P-value 0.05 as significant and P-value of >0.05 as insignificant or equivocal. Results: Out of 93 patients who developed incisional hernia 35 (37.6%) had postoperative wound infection. In control group 7 (7.8%) patients, out of 90 had post operative wound infection. The P value for post operative wound infection was < 0.01. It was statistically highly significant. In Study group chromic catgut, which is an absorbable suture, was used in 59 (63.4%) cases. Where as in control group chromic catgut was used in 10 (11.1%) patients and prolene was used in 80 (88.9%) patients. The P value for use of non absorbable suture material was < 0.01. It was statistically highly significant. There were 14 (15.05%) patients who were obese (weight more than 20% of the ideal weight) in the study group where as in control group 5 (5.6%) patients were overweight. The P value for obesity was >0.05. Its statistical significance was equivocal. Conclusion: Our study has shown that out of three incisional hernia factors under study, the wound infection and absorbable suture material were statistically most important factors. (P-value <0.01) and obesity was statistically insignificant (P-value >0.05).